Optimalisasi Pengenalan Angka dan Simbol Matematika Anak Usia Dini melalui Media Math Mystery Box - Siti Saniah; Jazariyah Jazariyah; Yayu Mega Purnamasari (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2026)
The ability to recognize numbers and mathematical symbols is an important skill that should be introduced in early childhood education, as it forms the foundation of early numeracy for subsequent stages of learning. However, in practice, preliminary findings indicate that many children experience difficulties in recognizing number symbols and mathematical symbols. These difficulties are influenced by several factors, including learning processes that are less varied and do not sufficiently support play-based activities. This study aims to optimize children’s ability to recognize numbers and mathematical symbols through the use of the Math Mystery Box learning media. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The study was carried out at RA Al-Muta’allimin, involving 14 children in Group B aged 5–6 years as research participants. Data were collected through observation, documentation, and children’s performance assessments. To determine the achievement of children’s developmental indicators, the data were analyzed using a descriptive quantitative approach. The results showed a significant improvement in children’s ability to recognize numbers and mathematical symbols. Based on observations during the pre-cycle stage, before the implementation of the intervention, the average achievement level of developmental indicators was in the BB (Not Yet Developed) category with a percentage of 28.6%. In Cycle I, the percentage increased to 54% with the MB (Beginning to Develop) category. Furthermore, in Cycle II, the percentage increased to 77.7%, indicating that children had reached the BSH (Developing as Expected) category. Therefore, the Math Mystery Box media can serve as an effective alternative learning medium to optimize early childhood’s ability to recognize numbers and mathematical symbols while creating a more engaging and meaningful learning process.